Sex-related association between smoke exposure and gallstones in a US population: a cross-sectional study - Xingyong Huang; Xuanyu Hao; Tingting Wang; Xiaoyue Zhang; Peng Wu; Lufan Shen; Yuanyuan Yang; Wanchuan Zhang; Kai Zhang (BMC Public Health)
Abstract Background Cholelithiasis are a condition that creates an economic and medical burden on society, and women are more susceptible to gallbladder stones. However, the effect of smoking on the development of gallstones remains controversial. No studies, to our knowledge, have discussed the association between smoke exposure and gallstones separately in men and women. We evaluated the association between smoking and gallstones in both sexes. Methods We conducted a cross-sectional analysis using data obtained from the National Health and Nutrition Examination Survey from 2017 to March 2020. The analysis was limited to individuals aged ≥ 20 years with complete information available. Self-reported smoking status, serum cotinine concentration, and self-reported gallstones conditions were combined to analyze the association of gallstones with smoking and cotinine concentration. Results Of the 6,982 participants, a total of 6.2% (212) men and 14.5% (512) women reported having gallstones. Logistic regression analysis showed smoking and high serum cotinine level were risk factors associated with gallstones among women, both in the model 1 (current smoker: odds ratio [OR] = 1.563, 95% confidence interval [CI] = 1.044–2.339, p = 0.032; former smoker: OR = 1.434, 95% CI = 1.116–1.842, p = 0.007; cotinine ≥ 3 ng/mL: OR = 1.800, 95% CI = 1.247–2.596, p = 0.005; and cotinine 0.05–2.99 ng/mL: OR = 1.640, 95% CI = 1.188–2.263, p = 0.005) and model 2 (current smoker: OR = 1.588, 95% CI = 1.015–2.483, p = 0.044; cotinine ≥ 3 ng/mL: OR = 1.825; 95% CI = 1.181–2.821, p = 0.011; and cotinine 0.05–2.99 ng/mL: OR = 1.509, 95% CI = 1.075–2.126, p = 0.022). However, the association was statistically insignificant in men. The subgroup analysis showed the robustness of the association. Conclusions This study indicates smoking and elevated serum cotinine levels may be risk factors associated with the development of gallstones. Notably, the associations were specifically observed among women. The findings suggest the significance of smoking in the incidence of gallstones, which may potentially provide insights for future research on strategies to prevent gallstones, particularly among women. The validation of these findings necessitates the conduction of large-scale, high-quality prospective studies.